Chickens - Miller, Sara Swan (New York Children's Press, 2000)
Describes the physical traits, lifestyle, and behavior of chickens and their role in providing humans with meat
Includes bibliographical references (p. 44) and index
Hurg
5 8
Keywords: Chickens